Examining the Relation of Gross National Income with Human Development Factors:a Study Of Brics Economy - Saryu (My University, 2017)
BRICS includes Brazil, Russia, India, China, South Africa. BRICS have become one of the most fascinating and active groups of the world which works with mutual co-operation. BRICS are newly developed industrialized countries with major population, increasing GDP, high rate of growth and have major impact on regional and global affairs. These nations had a large amount of unused capacity of labor and resources. BRICS does not aim at forming a political alliance or an official trade organization. It was developed with the objective of developing a new currency system and for increasing the dominance of developing countries in the international monetary organizations.; Seeing political and economic changes taking place on global level the BRICS economies have invested in new ventures and have initiated to have a good place on global level. After discussing the integration of BRICS with rest of the world the main objective of researchers is to analyse different components that affect the BRICS nation and to provide a comprehensive analysis to determine the weak and strong points of these nations. The data of various components affecting growth of different countries are taken. The growth of various heads of countries economic analysis is analyzed with help of trend rate of growth. To study these factors multiple regression model was used by taking gross national income (GNI) as dependent variable and maternal mortality rate (MMR), population, life expectancy at birth and improvement in sanitation facility as independent variable. Year to year growth arte was also calculated to examine the correct picture of all the components affecting the countries growth rate.
Master of Arts -Economics
Keywords: Gross National Income; BRICS; Human development factors